Face recognition system with vigenere cipher cryptography for document security - Sukri Sukri; Luluk Elvitaria; Wandiah Ayu Barus (Jurnal Mandiri IT, 2023)
The issue of data security and confidentiality is one of the most important aspects of an information delivery system. In this case, it is closely related to how important it is that the information be sent and received by interested parties. Information will no longer be useful if, in the middle of the delivery process, the information is intercepted or hijacked by unauthorized people. Computer security is something that is very important in this information age, especially for an organization or company. Data confidentiality The computer security problem is very important in this information age, especially for an organization or company because documents are some of the most important data for the continuity of the company's operations. The branch of science that studies ways to secure data is known as "cryptography." The Vigenère-Chiper algorithm is one of the cryptographic methods for encoding text. This study aims to create a cryptographic application that can encode text and send encrypted text over a network based on the Vigenère Chiper algorithm. This application performs cryptography on text in the form of letters, numbers, and symbols. The key used is alphanumeric, which is a combination of letters, numbers, and symbols. The results of this study are in the form of an application that can send encrypted text messages through a local area network (LAN) so that the confidentiality of the message can be maintained.